2021
DOI: 10.3390/healthcare9070787
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Life: Mediating Role in the Relationship between Depressive Symptoms and Coping Mechanisms

Abstract: The purpose of this study was to analyze the mediating role of life satisfaction in the relationship between fourteen coping strategies and depressive symptoms in the Portuguese population. To undertake this work, 313 Portuguese adults aged 18 to 70 years (M = 30.73; SD = 10.79) were invited to participate in this study. Their participation was completely voluntary, and participants granted and signed informed consent previously to the filling of the validated Portuguese questionnaires. These questionnaires me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
5
20
0
Order By: Relevance
“…Nonetheless, these psychological stress dimensions were positively and significantly associated with maladaptive coping. In consistency with our results, previous studies have shown that individuals with mood disorders used significantly more maladaptive coping strategies in workers during COVID-19 lockdown ( Mishra et al, 2021 ; Salazar et al, 2021 ) and after ( Almeida et al, 2021 ). Our results and these studies support our hypothesis that, as individuals experience feelings of self-doubt, severe despondency, and sadness, tend to void situations, events, damaging self-development, restricting growth, and failing to experience well-being.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nonetheless, these psychological stress dimensions were positively and significantly associated with maladaptive coping. In consistency with our results, previous studies have shown that individuals with mood disorders used significantly more maladaptive coping strategies in workers during COVID-19 lockdown ( Mishra et al, 2021 ; Salazar et al, 2021 ) and after ( Almeida et al, 2021 ). Our results and these studies support our hypothesis that, as individuals experience feelings of self-doubt, severe despondency, and sadness, tend to void situations, events, damaging self-development, restricting growth, and failing to experience well-being.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals who have dealt with stressful events such as COVID-19 lockdown and associated consequences may be more empathetic and understanding to the issues that other people may have faced ( Salazar et al, 2021 ). Thus, there could be some positive thinking that helps individuals deal with anxiety in a more adaptive manner, as the focus shifts from negative thoughts or concerns to active coping and searching for support ( Almeida et al, 2021 ). It is worth to mention that anxiety levels are nonetheless low (i.e., below midpoint) and that the correlation with adaptive coping is weak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal studies have shown that resilience has increased and the general population has found a surprising ability to adapt [ 56 , 57 ]. Coping mechanisms such as active attitudes, along with making plans, acceptance, and reinterpretation of reality are positively associated with LS [ 58 ]. Other factors that have helped to reduce stress are protective measures, psychological counselors [ 59 ], team support, stress monitoring, taking breaks regularly [ 60 ], knowledge of the disease [ 61 ], and things becoming easier [ 62 ].…”
Section: Discussionmentioning
confidence: 99%